HSP60 inhibits DF-1 apoptosis through its mitochondrial signal peptide - Shengliang Cao; Yanlan Li; Lele Chen; Xiaojing Lei; Xiujuan Feng; Yubao Li (Poultry Science)
HSP60 is implicated in many biological functions and plays a key role in maintaining oxidative stress and preserving mitochondrial integrity. Our previous study showed that HSP60 inhibits apoptosis. In this study, we further investigated the mechanism of apoptosis inhibition by HSP60. First, the CRISPR-Cas9 system was employed to establish the HSP60 knockout DF-1 cell line (DF-1-HSP60-KO), and the apoptosis level of DF-1-HSP60-KO cell line was assessed by flow cytometry and ELISA apoptosis kit. Then, the effect of knockdout of HSP60 on relevant apoptotic factors was assessed by Western blotting and RT-PCR analysis. The results showed that compared with the control DF-1 cells, HSP60 knockdout cells indicated significantly increased apoptosis rates, decreased Bax expression, and enhanced Caspase 3 expression. This suggests that the HSP60 knockout induces apoptosis by up-regulating Caspase 3 and down-regulating Bax expression. The structure of the HSP60 mitochondrial signal peptide (MIT) protein was predicted using Pymol software, which revealed that His amino acid at the 21st position affects its spatial structure. In addition, the transfection of HSP60 mutant protein (TB) into DF-1-HSP60-KO cells and induction with Bardoxolone MethyI significantly increased the apoptosis rates and reduced cell viability compared to the wild-type HSP60 group, inducing differential changes in genes such as Bax, Bak, and Bcl-2. Together, these findings suggest that the HSP60 MIT's His amino acid at site 21 modulates the levels of genes associated with the apoptosis signaling pathway, thereby inhibiting apoptosis. This study reveals the regulatory role of HSP60 in apoptosis through its mitochondrial signal peptide, which will have potential medical value.